Perbandingan Pertumbuhan dan Hasil Sorgum yang Diratun Asal Varietas Bioguma 1 - Harun, M. Umar; Sodikin, E.; Zaidan, Zaidan; Irmawati, Irmawati; Yakup, Yakup (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Harun, M.U., Sodikin, E., Zaidan, Z., Irmawati, I., & Yakup, Y. (2023). Comparison of growth and yield of ratooned sorghum from the bioguma 1 variety. In: Herlinda S et al. (Eds). Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 oktober 2023 (pp.129-134) Palembang : Penerbit &Percetakan Universitas Sriwijaya (UNSRI).Sorghum plants have begun to be developed into a national food commodity in anticipation of climate change. It is necessary to know various basic agronomic information about sorghum, especially the growth and yield of ratoon so that a sustainable and profitable crop cultivation package can be prepared. This research aimed to assess the vegetative and generative potentital of the Bioguma 1 sorghum variety as ratoon. This research was conducted at the research garden, Faculty of Agriculture, Universitas Sriwijaya, Indralaya from February 2023 until August 2023. The methodology used was non-experimental. Sampling was carried out randomly for 80 plants from a population of 1600 plants. The research results showed that there was a decrease in vegetative and generative growth of ratoon sorghum compared to its parent. Decreases occurred in stem length (21%), number of leaves (50%), shoot dry weight (59%), panicle weight (61%), and number of seeds (22%). The decrease in generative components was greater than vegetative in ratoon sorghum plants.